Effect Of Slow Deep Breathing Therapy On Hypertension Levels In Elderly - Eva Dwi Ramayanti; Susmiati (Master of Public Health Program Universitas STRADA Indonesia, 2024)
Elderly is someone aged 45-60 and above. In old age, a person experiences a degenerative process to be more susceptible to disease, hypertension. Hypertension is a condition in which the blood vessels have persistently raised pressure. One of the complementary therapies to control blood pressure is slow deep breathing therapy. This therapy has through breathing. The purpose of this study was to prove whether there was an effect of slow deep breathing therapy on hypertension levels in the elderly. This research is a Pre Experiment. This study's population was 17 people, and the number of samples was 15 people selected by the Simple Random Sampling method. The statistical test used in this study is the Wilcoxon Test. The study results concluded that there is an effect of slow deep breathing therapy on hypertension level. There is a decrease in blood pressure after being given slow deep breathing exercise therapy.